Fast perceptual learning induces location-specific facilitation and suppression at early stages of visual cortical processing - Wang, Yajie; Qu, Zhe; Wang, You; Sun, Mingze; Mao, Mengting; Ding, Yulong (Frontiers in Human Neuroscience, 2025)
Tens of minutes of training can significantly improve visual discriminability of human adults, and this fast perceptual learning (PL) effect is usually specific to the trained location, with little transfer to untrained locations. Although location specificity is generally considered as a hallmark of visual PL, it remains unclear whether it involves both facilitation of trained locations and suppression of untrained locations. Here we developed a novel experimental design to investigate the cognitive neural mechanism of location specificity of fast PL. Specifically, we manipulated attentional settings and recorded event-related potentials (ERPs) in both the training and tests. To get reliable location-specific PL effects on early ERPs, we adopted a new approach involving analysis of contralateral-minus-ipsilateral P1 (P1c-i). ERP results showed that tens of minutes of training not only increased the late P1c-i (~100–120 ms) evoked by targets at the trained location, but also decreased the early P1c-i (~75–95 ms) evoked by distractors at the untrained location, both of which were location specific. Moreover, comparison between the pretest and posttest revealed that the suppression effect of early P1c-i preserved even when the untrained location became target location, whereas the facilitation effect of late P1c-i appeared only when the trained location remained actively attended. These findings provide the first evidence that fast PL induces both location-specific facilitation and location-specific suppression at early stages of visual cortical processing. We speculate that while the facilitation effect indicates more efficient allocation of voluntary attention to the trained location induced by fast PL, the suppression effect may reflect learning-associated involuntary suppression of visual processing at the untrained location. Several confounding factors with regard to the early ERP effects of PL are discussed, and some important issues worth further investigation are proposed.